Gate-tunable large magnetoresistance in an all-semiconductor spin valve device - M. Oltscher (Nature Portfolio, 2017)
The development of spin field effect transistors has been hampered by the low magnetoresistance in the semiconductor spin valve. Here the authors report large and tunable magnetoresistance in a lateral 2DES-based spin valve geometry due to finite electric field effects at the ferromagnet-semiconductor interface.